2017
DOI: 10.1007/s11096-017-0484-9
|View full text |Cite
|
Sign up to set email alerts
|

Use patterns of first-line inhibitors of tyrosine kinase and time to change to second-line therapy in chronic myeloid leukemia

Abstract: Background Chronic myeloid leukemia (CML) has a low incidence but a high burden of disease, and is treated with high-cost tyrosine kinase inhibitors (TKI). Objective To determine the time from the start of a first-line TKI until it passes to second-line, and to establish the reasons for the change of therapy time. Setting Patients with Philadelphia-positive CML treated with some TKI. Methods Retrospective cohort study, between January 1 2007 and July 31 2015, with information obtained from medical records, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…In fact, the median duration of treatment was 1 year shorter for nilotinib compared with imatinib, although there was no statistical significance (4.55 years [IQR 1.39-7.89] vs. 3.59 years [IQR 2.23-4.76], p = 0.402). Nevertheless, two recent national and international observational studies by Castagnetti et al and Machado-Alba and Machado-Duque [24,25] found similar results, reporting a significantly higher proportion of switches in patients treated with imatinib compared with second-generation TKIs, mainly due to resistance. On the other hand, in our study most switches from imatinib were due to severe treatment intolerance.…”
Section: Discussionmentioning
confidence: 66%
“…In fact, the median duration of treatment was 1 year shorter for nilotinib compared with imatinib, although there was no statistical significance (4.55 years [IQR 1.39-7.89] vs. 3.59 years [IQR 2.23-4.76], p = 0.402). Nevertheless, two recent national and international observational studies by Castagnetti et al and Machado-Alba and Machado-Duque [24,25] found similar results, reporting a significantly higher proportion of switches in patients treated with imatinib compared with second-generation TKIs, mainly due to resistance. On the other hand, in our study most switches from imatinib were due to severe treatment intolerance.…”
Section: Discussionmentioning
confidence: 66%
“…A total of seven studies met inclusion criteria and evaluated the safety of TKIs in real-world patients. 7 , 10 , 11 , 13 , 19 , 21 , 22 Five landmark phase II or III clinical trials were analyzed for safety outcomes. 4 6 , 15 , 17 …”
Section: Resultsmentioning
confidence: 99%
“…A total of seven studies met inclusion criteria and evaluated the safety of TKIs in real-world patients. 7,10,11,13,19,21,22 Five landmark phase II or III clinical trials were analyzed for safety outcomes. [4][5][6]15,17 Changes and discontinuations of TKI therapy were the most commonly reported measures of safety and tolerability in real-world studies.…”
Section: Safetymentioning
confidence: 99%
“…Among these, 351 articles were excluded after title screening and the abstract of the 784 remaining papers was assessed. Finally, 461 publications were excluded following the eligibility criteria and thus, 323 articles that had interpretable data and fulfilled the eligibility criteria were used for data extraction…”
Section: Resultsmentioning
confidence: 99%
“…A pharmacy dispensing company (Audifarma SA) was identified in the SLR as the most commonly used database for RWE 34,42,61,63,72,73,94‐98,100‐109,111‐115,117,118,120,122‐131,134‐141,163,168,242,301,310 . It contains demographic data, diagnosis by ICD‐10, and drug dispensation records coded by the Anatomical Therapeutic Chemical (ATC) classification, which can be used to identify comorbidities, drug‐to‐drug interactions, medication errors, adverse events, and calculate adherence rates.…”
Section: Resultsmentioning
confidence: 99%